1974
DOI: 10.1172/jci107802
|View full text |Cite
|
Sign up to set email alerts
|

3α-Androstanediol Kinetics in Man

Abstract: A B S T R A C T Kinetics of 5a-androstane-3a, 17p-diol (3a-diol) were studied in man. Clearance than expected from information on in vitro binding in plasma. The kinetic data is of interest since 3a-diol has a calculated inner pool (Vi) volume of 12-14 liters, similar to 1713-hydroxyandrost-4-en-3-one (testosterone) and 5a-androstan-1713-ol-3-one (dihydrotestosterone), but the calculated outer pool (V2) of 33.5 liters is very large as are the metabolic rate and transfer constants. In contrast to testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 23 publications
(20 reference statements)
1
22
0
Order By: Relevance
“…In man, secreted testosterone is peripherally converted into DHT and 3adiol by nongonadal tissues and a majority of both androgens in blood are derived from secreted testosterone (11,12). The importance of these observations was increased when it became clear that DHT conversion did not occur in muscle (13), and we have demonstrated that both DHT and 3adiol are derived from conversion in extrasplanchnic tissue (14).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In man, secreted testosterone is peripherally converted into DHT and 3adiol by nongonadal tissues and a majority of both androgens in blood are derived from secreted testosterone (11,12). The importance of these observations was increased when it became clear that DHT conversion did not occur in muscle (13), and we have demonstrated that both DHT and 3adiol are derived from conversion in extrasplanchnic tissue (14).…”
mentioning
confidence: 70%
“…[14C]testosterone and [3H]3adiol were given by constant infusion over a 2-h period as described (11,12 for correction of losses and the plasma extracted with solvent as described (14). The dried extracts were then chromatographed on a celite column (18), collecting testosterone, DHT, and 3adiol fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RIA measurements of 5α-androstan-3α,17β-diol glucuronide levels revealed that this metabolite was also present at background levels in the sera of type 2-deficient and type 1-and 2-deficient mice. This steroid is produced from DHT by reductive 3α-hydroxysteroid dehydrogenases, and its presence in the plasma of humans is directly proportional to the level of DHT (34)(35)(36). Inasmuch as these findings translate to the mouse, the absence of 5α-androstan-3α,17β-diol glucuronide from the knockout animals suggests that circulating levels of DHT are, in fact, very low or absent.…”
Section: Discussionmentioning
confidence: 96%
“…Studies in the rat, dog, marsupial and human also indicate that circulating 3α-diol can be oxidized back to 5α-DHT (Orlowski et al, 1983;Walsh and Wilson, 1976;DeKlerk et al, 1979;Jacobi et al, 1977; Liehy et al, 2001;Shaw et al, 2000;). In fact 50% of an administered dose of 3α-diol in humans was converted to 5α-DHT within the prostate, indicating that the back conversion is significant in androgen action (Horst et al, 1975;Kinouchi and Horton 1974). Backdoor pathways to 5α-DHT using 3α-diol as a precursor have been proposed in which the production of DHT "by-passes" the formation of Δ 4 -androstene-3,17-dione and testosterone, (Auchus, 2004).…”
mentioning
confidence: 99%